Adalimumab reduces hand bone loss in rheumatoid arthritis independent of clinical response: Subanalysis of the PREMIER study - Elden Aake; Kälvesten Johan; Kvien Tore K; Hoff Mari; Kavanaugh Arthur; Haugeberg Glenn (BMC Musculoskeletal Disorders, 2011)
Abstract Background Anti-TNF therapy has been shown to reduce radiographic joint damage in rheumatoid arthritis (RA) independent of clinical response. This has previously not been examined for periarticular bone loss, the other characteristic feature of bone involvement in RA. The objective of this study was to examine if treatment with the TNF-α inhibitor adalimumab also could reduce periarticular bone loss in RA patients independent of disease activity. Methods RA patients were recruited from the PREMIER study and included 214 patients treated with methotrexate (MTX) plus adalimumab and 188 patients treated with MTX monotherapy. Periarticular bone loss was assessed by digital X-ray radiogrammetry metacarpal cortical index (DXR-MCI). Change in DXR-MCI was evaluated in patients with different levels of clinical response, as assessed by changes in DAS28 score at 52 weeks and in mean C-reactive protein (CRP) levels during follow-up. Results In the MTX group, there was a greater median DXR-MCI loss among patients with moderate and high disease activity compared to those in remission or with low disease activity (-3.3% vs. -2.2%, p = 0.01). In contrast, periarticular bone loss was independent of disease activity (-1.9% vs. -2.4%, p = 0.99) in the combination group. In the MTX group patients with a mean CRP of ≥ 10 mg/l lost significantly more DXR-MCI than patients with low CRP (-3.1% vs. -1.9%, p <0.01) whereas in the combination group no significant differences between the two CRP groups was seen (-2.4% vs. -2.0%, p = 0.48). Conclusion Adalimumab in combination with MTX reduces periarticular bone loss independently of clinical response. These results support the hypothesis that TNF-α stimulates the osteoclast not only by the inflammatory pathway but do also have a direct effect on the osteoclast. Trial Registration ClinicalTrials (NCT): NCT001195663